Implementation of Green Hospital Concept in Solid Medical Waste Management - Desak Putu Risky Vidika Apriyanthi; Ni Putu Widayanti; Ayu Saka Laksmita (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hospitals are one of the institutions that use considerable energy and contribute the largest amount of waste. To reduce the impact, initiatives have emerged in the form of greening hospitals for effective use of resources. Green Hospital is a hospital concept that is designed by empowering the potential of nature as the main resource so that it is friendly to the environment and saves energy expenditure. The existence of Green Hospital is needed to overcome climate change that can cause human health problems and the environment, because hospitals are one of the contributors to pollution. In Indonesia, Green Hospital is still a concept that emphasizes effective and efficient use of water and electrical energy, as well as environmentally sound waste management. The purpose of this study is to analyze solid medical waste management in Saraswati Dental and Oral Hospital Denpasar in realizing the Green Hospital concept. This research is qualitative. Data were collected by in-depth interviews with1 staff at the Environmental Health Installation and 3 staff of cleaning service, observation, and document review. Data were analyzed by data reduction, data presentation, and conclusion. Data validity used source triangulation and method triangulation. Medical waste management in Saraswati Dental & Oral Hospital Denpasar is generally in has been accordance with the Indonesian health regulation No. 1204/2004, but does not yet have a policy or direction to realise Green Hospital. To achieve Green Hospital, hospitals can start by making policies to implement non-medical waste minimization and increasing the number of personnel in the field of medical and non-medical waste management.